Surface Alloying of Internal Surfaces of Low‐Carbon Steel Castings through Incorporation of Nickel, Nickel and Chromium, and 316L Stainless Steel Powders to Mold and Core Surfaces. Issue 4 (27th October 2021) - Kordijazi, Amir; Beining, Michael; Rane, Kaustubh; Behera, Swaroop; Rohatgi, Pradeep
Abstract : A surface alloying technique is developed to enrich the internal surfaces of low‐carbon steel casting with nickel or nickel and chromium. This unique technique involves the incorporation of nickel (Ni), nickel and chromium (Ni + Cr), or stainless steel (SS) powders into a slurry, and then applying the slurry onto the surface of cores used in sand molds which comes in contact with molten metal during casting. Various properties, including coating thickness, composition, microstructural phases, surface hardness, and corrosion resistance of the surface‐alloyed layer, are studied. The internal surface of the substrate metal is enriched with nickel and chromium, up to 16.32 wt% Ni or 7.79 wt% Ni and 15.85 wt% Cr. Optical microscopy shows that the surface‐enriched layer is continuous over the entire surface of the casting and ranges in thickness from 229 to 1342 μm. When alloyed with Ni and SS powders, the surface‐alloyed layers demonstrate a dendritic solidification microstructure, suggesting complete dissolution of powders in steel followed by solidification. While the substrate primarily displays pearlitic and ferritic structures, simulation and X‐ray diffraction confirm the presence of austenite and ferrite in the surface‐alloyed layer when Ni + Cr is used. Microhardness testing and corrosion studies show significant improvement after surface alloying. Abstract : A novel and inexpensive surface alloying technique is developed to enrich the internal surface of a low‐carbon steel casting with nickel or nickel plus chromium, leading to a harder and more corrosion‐resistant surface.